2007
DOI: 10.1111/j.1468-2419.2007.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Returning to flight: simulation‐based training for the US National Aeronautics and Space Administration's Space Shuttle Mission Management Team*

Abstract: Following the tragic loss of Columbia in early 2003, executives at the National Aeronautics and Space Administration implemented a simulation-based training program to facilitate the development of the Space Shuttle Mission Management Team (MMT). This article discusses the findings from an evaluation of two multi-day simulation training events. The results of both evaluations suggested that MMT members: (1) possessed shared beliefs in their joint capabilities to execute their core competencies;(2) were motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…team training studies (e.g., Ellis, Bell, Ployhart, Hollenbeck, & Ilgen, 2005;E. E. Entin, Serfaty, & Deckert, 1994;Klein, Stagl, Salas, Parker, & Van Eynde, 2007). Given the abundance of theoretical support and empirical evidence speaking directly to the usefulness of team training, the following hypothesis is advanced:…”
Section: Does Team Training Work?mentioning
confidence: 99%
“…team training studies (e.g., Ellis, Bell, Ployhart, Hollenbeck, & Ilgen, 2005;E. E. Entin, Serfaty, & Deckert, 1994;Klein, Stagl, Salas, Parker, & Van Eynde, 2007). Given the abundance of theoretical support and empirical evidence speaking directly to the usefulness of team training, the following hypothesis is advanced:…”
Section: Does Team Training Work?mentioning
confidence: 99%
“…Thirteen of the articles used students or recent graduates at least in part for their sample [68,69,[74][75][76][77][78][79][80][81][82]84,85]. Ten of the studies directly measured job-related skills or tasks in some way as an outcome measure [68][69][70][71][72]74,[77][78][79]81]. Five measured reactions to the simulation as part of their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a very different setting, Klein et al (2007) found support for SBT as a promising approach for training the US National Aeronautics and Space Administration's (NASA) space shuttle mission management team. After undergoing SBT, team members had shared beliefs in their abilities to perform as a team, showed increased levels of motivation and readiness, performed at target levels, and had favorable reactions to the training programthey were satisfied with it and believed it was useful for improving their performance.…”
Section: Is Simulation-based Training Effective?mentioning
confidence: 99%